Analisis Resepsi Khalayak Tentang Stigma Orang Dengan Skizofrenia Pada Tayangan Youtube CXO MEDIA “Perspektif” Episode 23 - Devi Salsabillah; Retno Dyah Kusumastuti (Brand Communication, 2022)
This study aims to find the meaning formed by the audience about the stigma of people with schizophrenia (ODS) through YouTube shows on the CXO Media Channel on the program “Perspektif” Episode 23 – Semua Penyakit Ada Obatnya. The video was chosen by the researcher as the object of research because it is considered one of the videos devoted to discussing what schizophrenia is and the stigma attached to the sufferer. As a chronic disease, people often ignore empathy for people with schizophrenia. Therefore, this study seeks to find out how the phenomenon of stigma against People with Schizophrenia (ODS) on CXO Media's YouTube show “Perspektif” Episode 23 - All Diseases Has a Cure by using the encoding-decoding model audience reception theory initiated by Stuart Hall. This study uses a qualitative descriptive method. The data collection technique was done by the purposive sampling technique. The results showed that from the five informants, there were 4 (four) informants belonging to the dominant hegemonic position and 1 (one) informant belonging to the negotiating position. The differences in meaning conveyed by the five informants were based on the different backgrounds possessed by each informant, including life experience, beliefs religion, socio-geographic (residential environment), level of knowledge or education, and how to use social media